(untitled) (Vietnam Journal of Community Medicine, 2026)
Solitary fibrous tumor of the pleura (SFTP) is a rare neoplasm, accounting for less than 5% of all primary pleural tumors. While typically benign and slow-growing, SFTP can reach a massive size, leading to severe compression of mediastinal structures and manifest respiratory symptoms. Giant SFTP (gSFTP) is defined as an SFTP measuring over 15 cm or occupying more than 40% of the affected hemithorax. We report a case of a giant benign SFTP in a 64-year-old female patient who presented with progressive dyspnea and right-sided chest pain. Chest computed tomography (CT) revealed a large, solid mass occupying almost the entire right pleural cavity, without invasion into the lung parenchyma or mediastinal structures.The pathology report from the preoperative needle biopsy revealed a solitary fibrous tumor of the pleura. The patient underwent complete tumor resection via a right thoracotomy. The excised mass measured 21x21 cm and weighed over 2 kg. Histopathological examination confirmed a solitary fibrous tumor of the pleura. Postoperatively, the patient recovered well with no signs of recurrence during a 12-month follow-up period. The patient was then instructed to continue with regular check-ups. This case highlights the clinical importance of early recognition and prompt surgical management of giant pleural tumors, despite their rarity.